Politeness Strategies in Ugandan English: Making Requests and Responding to Thanks - Isingoma, Bebwa (Brno Studies in English, 2021)
This study examines politeness strategies and specific expressions employed by Ugandans when making requests and responding to thanks, against the backdrop that contact phenomena, as one of the key factors that characterize L2 varieties such as Ugandan English, make it virtually inevitable to have peculiarities in this respect. Specifically, in relation to the illocutionary acts of request, Ugandan English relies more on direct strategies (due to substrate influence), with various idiosyncratic mitigating devices such as the use of the past progressive with performative verbs, the use of the lexical mitigator first with imperatives, and the use of verbs with inherent supplicatory semantics in the imperative mood. As regards responses to thanks, while there is a clear preference for exonormative standards, formulae arising from substrate influence are visibly present, while several of the formulae used in L1 English (e.g. Standard British English) are not used in Ugandan English.
Keywords: Requests; Responses to thanks; Modality; Direct strategies; Exonormativity